Penerapan Peraturan Sanksi Disiplin Bagi Aparatur Sipil Negara di Lingkungan Pemerintah Daerah Badan Kepegawaian Daerah Kabupaten Gorontalo Utara - Moonti, Roy Marthen; Polidu, Irwan (Universitas Gorontalo, 2018)
Implementation of disciplinary sanction regulation for state civil apparatus within the local government of regional civil service employee education and training in northern gorontalo and Constraints faced by the Regional Personnel Board of Education and Training Kabupaten Gorontalo Utara in increasing the application of disciplinary sanction regulation for the State Civil Apparatus. To know the implementation of disciplinary sanction regulation for civil state apparatus in the local government of civil service agency of education and training area of north gorontalo district and to know the obstacles faced in Regional Personnel Board of Education and Training of North Gorontalo Regency in increasing the application of disciplinary sanction regulation for State Civil Apparatus. This type of research is descriptive normative research that is a research that emphasizes on the real condition of the field which then synced on the rules - the rule of law, rule of law law, the opinions of scholars and regulations related to the research. This research was conducted to obtain information, explanation and data on the application of disciplinary sanction regulation for civil apparatus of state environment of local government of north gorontalo district. the application of disciplinary sanction regulation for state civil apparatus within the local government of the regional civil service agency of education and training of northern gorontalo district is in accordance with prevailing provisions, namely PP. 53 of 2010 on the discipline of civil servants and obstacles encountered in the Regional Personnel Board Education and Training District of North Gorontalo in increasing the application of disciplinary sanctions regulation for the State Civil Apparatus that is the length of the reporting process from the prosecutor to the Regional Personnel Board of Gorontalo Utara for specific disciplinary sanctions the case of a criminal offense. The mistake is due to the State's Civil Apparatus itself, which lacks the discipline of the civil state apparatus, the duration of the disciplinary sanction process itself due to the length of the process of applying disciplinary sanction regulation in accordance with pp 53 of 2010.